Pengaruh kepatuhan perawat terhadap standar prosedur operasional pemasangan kateter Di RS PKU Muhammadiyah Gombong. - Ratih Lestari Utami (MRS 14 UMY 132, 2014)
xii ABSTRACT THE EFFECT OF NURSE COMPLIANCE TO STANDARD OPERATING PROCEDURE FOR CATHETER INSERTION IN RS PKU MUHAMMADIYAH GOMBONG Background: Minister Regulation No. 012 of 2012 mentions the hospital accreditation that hospitals should make efforts to improve the quality of care and patient safety one of way to prevent and control infections in the hospital. Prevention efforts can to do by applying the Standard Operating Procedure (SOP) in every action of nurses (Pusdiknakes, 2004). The actions which not appropriate to the procedure, can cause Hospital Acquired Infection (HAIs). Objective: To determine the level of compliance of nurses on spo catheter use. To determine the effect of reciprocity, commitment, social proof, liking, authority, and scarcity of the catheter SPO with the level of nurse compliance at PKU Muhammadiyah Gombong Hospital. Methods: This study was an analytical cross-sectional approach whose results are presented in descriptive multivariate analysis followed using Multiple Regression. The subjects were nurses on duty in the ward class III and emergency room PKU Muhammadiyah Gombong Hospital. The research instrument was a questionnaire and observation. Results and Discussion: Nurses did not execute properly catheter so well with compliance rate of 0%. This is because nurses are accustomed forget to make some point and no one warned. The results obtained by the analysis of the value of Adjusted R2 of 0.040. This suggests that reciprocity, commitment/consistency, social proof, liking, authority and scarcity of nurses contributes to adherence by 4%, which means it does not contribute significantly to the compliance of nurses in implementing SPO catheter at PKU Muhammadiyah Gombong Hospital. Conclusion: Reciprocity, commitment/consistency, social proof, liking, authority and scarcity do not contribute significantly to the compliance of nurses in implementing SPO catheter. Nurses did not execute properly catheter so well with compliance rate of 0%. Recommendations need to do is nurse Improving compliance by increasing supervision, monitoring and motivation of nurses in the compliance of standard operating prosedure of urinary catheter insertion. Keywords: the compliance of nurse, standard operating procedures of catheter